Exploring Functional Properties of Mantis Shrimp (Miyakella nepa) Protein Powder for Sustainable Food Applications - Varsha, D.; Balange, A. K.; Layana, P.; Deepitha, R. P.; Iburahim, D. Abuthagir; Joshi, S. A.; Gore, S. B. (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted from January to August, 2023 at the Central Institute of Fisheries Education, Mumbai, India, to investigate the potential of mantis shrimp (Miyakella nepa) as a resource for developing value-added food products. The protein powder from alkaline solubilization showed a higher water-holding capacity (2.39 ml g-1) than phosphate buffer extraction (0.79 ml g-1), while phosphate buffer extraction exhibited greater oil-holding capacity (2.04 g g-1) compared to alkaline solubilization (1.81 g g-1). Emulsion capacity was 47.02% for alkaline solubilization and 52.38% for phosphate buffer extraction, with phosphate buffer extraction demonstrating better emulsion stability (38.98%) after heating at 80°C for 30 minutes. For foaming properties, alkaline solubilization had a higher foaming capacity (201.66%), whereas phosphate buffer extraction showed superior foaming stability (32.87%). Both powders achieved maximum solubility at pH 12, with solubility at pH 7 being 22.44% for alkaline solubilization and 9.25% for phosphate buffer extraction. Bulk density was 0.30 g ml-1 for alkaline solubilization and 0.34 g ml-1 for phosphate buffer extraction, indicating slight variations in physical characteristics between the two protein powders. The differences observed in water and oil-holding capacities indicated variations in hydrophilic and hydrophobic interactions within the extracted proteins. Emulsion and foaming characteristics reflected their potential use in formulated food products requiring stable emulsions or aerated textures. Differences in bulk density could influence powder handling, packaging, and application in various product formulations, highlighting functional versatility between extraction methods.